Presurgical nasoalveolar molding as an effective adjuvant therapy to aid rehabilitation cleft malformations in newborn - Hastinawaty; Vinsensia Launardo (Indonesia Prosthodontic Association, 2023)
Cleft lip and palate (CLP) is a congenital anomaly that commonly occurs in the mouth and maxilla. Cleft lip and/or cleft palate can alter a child's appearance, affect pronunciation, swallowing and chewing, and lead to varying de-grees of psychological damage in growing children involving the upper lip, hard palate, soft palate and nose. The goal of primary closure of CLP is to ensure normal and symmetrical lips and nose. Presurgical nasoalveolar mold-ing (PNAM) is a non-surgical method reshapes the lips, alveoli, cleft palate, and cleft nose to minimize the severity of cleft lip deformity prior to cleft palate and primary cleft palate surgery. This article is aimed to review management of CLP in newborn using PNAM. It is concluded that PNAM is an effective adjuvant therapy to reduce preoperative hard and soft tissue cleft malformations because helps improve nasal aesthetics, reduce cleft size, and correct the maxil-lary arch with reduction of alveolar size and cleft palate.